Role of ClpB From Corynebacterium crenatum in Thermal Stress and Arginine Fermentation - Huang, Mingzhu; Zhao, Yue; Feng, Lin; Zhu, Lingfeng; Zhan, Li; Chen, Xuelan (Frontiers in Microbiology, 2020)
ClpB, an ATP-dependent molecular chaperone, is involved in metabolic pathways and plays important roles in microorganisms under stress conditions. Metabolic pathways and stress resistance are important characteristics of industrially -relevant bacteria during fermentation. Nevertheless, ClpB-related observations have been rarely reported in industrially -relevant microorganisms. Herein, we found a homolog of ClpB from Corynebacterium crenatum. The amino acid sequence of ClpB was analyzed, and the recombinant ClpB protein was purified and characterized. The full function of ClpB requires DnaK as chaperone protein. For this reason, dnaK/clpB deletion mutants and the complemented strains were constructed to investigate the role of ClpB. The results showed that DnaK/ClpB is not essential for the survival of C. crenatum MT under pH and alcohol stresses. The ClpB-deficient or DnaK-deficient C. crenatum mutants showed weakened growth during thermal stress. In addition, the results demonstrated that deletion of the clpB gene affected glucose consumption and L-arginine, L-glutamate, and lactate production during fermentation.